KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI UJUNG TOMBAK DALAM MEMPERBAIKI KWALITAS SEKOLAH - NI NYOMAN PERNI (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Qualified teachers are required to have a deep and extensive knowledge of science in accordance with the field of science owned. One area of science that deserves attention is the science of Education. The existence of teachers as a sub-system of the field of study is actually very important to build a